2018
DOI: 10.1016/j.jfca.2017.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus fermentation of jussara pulp leads to the enzymatic conversion of anthocyanins increasing antioxidant activity

Abstract: Bacteria possessing an enzymatic system able to metabolize anthocyanins may play a major role in the production of compounds with different bioavailability and biological activity. In this study, Lactobacillus and Bifidobacterium strains were screened for the enzymatic activities of α-galactosidase, β-galactosidase and βglucosidase. These strains were also screened for their ability to convert the anthocyanins from jussara. The nine evaluated strains produced at least two of the three enzymes; they were also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…In addition, gene sequencing of human faecal GM indicates that the richness of microbes from Lachnospiraceae family: Blautia, Dorea and Ruminococcus can positively influence the levels of glutamate and BCAA resulting in obese features while that of bacterium SHA-98 induces the opposite effect (Ottosson et al 2018). Further report shows that Lactobacillus delbrueckii strains are capable of converting anthocyanins found in berries, cherries and red cabbage to protocatechuic acid (PCA) (Braga et al 2018), which is an essential metabolite associated with the suppression of pro-inflammatory markers by elevating insulin receptor substrate-1 and protein kinase B phosphorylation in obese individuals (Ormazabal et al2018). Another biometabolite of anthocyanins, ferulic acid, produced by Lactobacillus fermentum has also been shown to regulate energy metabolism by adjusting the target of rapamycin (TOR) signalling pathway (Westfall et al 2019).…”
Section: Gm and Circulating Metabolitesmentioning
confidence: 99%
“…In addition, gene sequencing of human faecal GM indicates that the richness of microbes from Lachnospiraceae family: Blautia, Dorea and Ruminococcus can positively influence the levels of glutamate and BCAA resulting in obese features while that of bacterium SHA-98 induces the opposite effect (Ottosson et al 2018). Further report shows that Lactobacillus delbrueckii strains are capable of converting anthocyanins found in berries, cherries and red cabbage to protocatechuic acid (PCA) (Braga et al 2018), which is an essential metabolite associated with the suppression of pro-inflammatory markers by elevating insulin receptor substrate-1 and protein kinase B phosphorylation in obese individuals (Ormazabal et al2018). Another biometabolite of anthocyanins, ferulic acid, produced by Lactobacillus fermentum has also been shown to regulate energy metabolism by adjusting the target of rapamycin (TOR) signalling pathway (Westfall et al 2019).…”
Section: Gm and Circulating Metabolitesmentioning
confidence: 99%
“…PCA has already been proven as the gut microbiota metabolite of C3G [60], as Lactobacillus and Bifidobacterium have the maximum ability to produce the β-glucosidase so that anthocyanins are transformed to PCA [61]. Lactobacillus and Bifidobacterium are also observed to produce p-coumaric acid and FA under different carbon sources [57,62], while Bacillus subtilis and Actinomycetes are involved in the bioconversion of VA to guaiacol [63].…”
Section: Crosstalk Between Gut Microbiota and C3gandc3g-msmentioning
confidence: 99%
“…Among the bioactive compounds constituting fruits and vegetables, anthocyanins are particularly remarkable, due to their potential industrial application as natural pigments. Likewise, this bioactive compound has shown several positive effects over human health, as numerous studies reported in the latest years [19,26,27]. The main property described regards their antioxidant capacity, since this pigment acts as free radical scavengers, which is frequently linked to the prevention of chronic diseases [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in our group showed that jussara, besides the colorant power provided by the anthocyanins, is accounted for in several beneficial results from a perspective of health and well-being [27,[30][31][32]. Jussara pulp has been recognized as a superfood due to its composition, mainly, for the high concentration of anthocyanins and other phenolic compounds; in fact, these bioactive compounds are considered an attractive source of pigments and also means to ward off several diseases [27,33,34]. In this context, the pulp as a whole can be used in food preparations to confer color and beneficial biological effects.…”
Section: Introductionmentioning
confidence: 99%